Desenvolvimento de dispersões sólidas e nanopartículas poliméricas mucoadesivas de Zidovudina e avaliação da interação biológica com a mucosa intestinal - Pedreiro, Liliane Neves [UNESP] (2015)
Zidovudine (AZT) is the most widely used drug alone or in combination with other antiretroviral agents for the treatment of AIDS, caused by the HIV virus. The low AZT bioavailability is the great challenge to be overcome to optimize its performance in oral therapy, since its high rate of hepatic metabolism and low permeability results in the need for high doses of the drug. In addition, this drug is substrate of the efflux mechanism mediated by P-glycoprotein in the gut, which further decreases its bioavailability. Thus, solid dispersions (SD) and polymeric nanoparticles (NP) were developed by complexation polyelectrolyte with different ratios between the drug and the polymers chitosan (CS) and hydroxypropyl methylcellulose phthalate (HP). The drug content in the SDs (around 98%) was higher than in NPs (about 65%). The in vitro release assays performed in HCl 0.1 mol/l (pH 1.2) showed that polymeric complexation and drug entrapment reduced the AZT rates release in both SDs (26 to 50%) and NPs (around 60%), and in phosphate buffer 50 m mol/l (pH 7.4), both modified the drug release until 240 minutes. The particle size determination confirmed obtaining micro systems (around 100 micron) and nanoparticles (around 400 nm) and zeta potential showed the negative surface of SDs and the positive charge of NPs. DSC and XRD data showed that AZT remained molecularly dispersed in both systems and the DSs had an amorphous structure, while the NPs showed structure crystalline predominantly. The IR spectroscopy showed in both SDs and NPs the formation of bonds between CS and the HP without changing the structure of AZT. The NPs showed higher liquid absorption capacity (until 260%) relative to SDs (until 160%) in different pH values, while SDs presented higher mucin adsorption capacity. The SDs and NPs mucin adsorption occurs according to the mechanism of Freundlich and Langmuir, respectively. Intestinal permeability assay showed the influence of SD to ...